You first need to distribute the (-5) and the (2) on both sides of the equation.
Then combine like terms, the (x)s and the numbers.
Isolate the variable (x) onto one side.
Solve for x
I need help on the following Problem:
3x-5(3x-7)=2(x+9)+45
4 answers
this is what I got so far....
3x-5(3x-7)=2(x+9)+45
3x-15x+35=2x+18+45
-12x+35=2x+63
-35=2x+63-35
-12x=2x+28
-2x=28
-14x=28
-x=-2
Is this correct?
3x-5(3x-7)=2(x+9)+45
3x-15x+35=2x+18+45
-12x+35=2x+63
-35=2x+63-35
-12x=2x+28
-2x=28
-14x=28
-x=-2
Is this correct?
3x-5(3x-7)=2(x+9)+45
3x-15x+30 = 2x + 18 + 45 (distribute)
-12x + 30 = 2x + 63 (combine like terms)
------------------
30 = 14x + 63 (further combine like terms--additive property)
-33=14x (move 63 to other side [giving you -33] *simplify*
x= -2.35 (simplify, divide 14 into -33(to isolate variable)
Please check math as I may have gotten it wrong.
Hope that helped!
3x-15x+30 = 2x + 18 + 45 (distribute)
-12x + 30 = 2x + 63 (combine like terms)
------------------
30 = 14x + 63 (further combine like terms--additive property)
-33=14x (move 63 to other side [giving you -33] *simplify*
x= -2.35 (simplify, divide 14 into -33(to isolate variable)
Please check math as I may have gotten it wrong.
Hope that helped!
woops looks like my math was wrong-- mm you're answer is correct. Nice job at showing you're work!